Granular cell tumor of the stellate ganglion presenting with Horner's syndrome. Issue 9 (September 2015) - Burke, Shane M.; Wein, Richard O.; Brinckerhoff, Laurence H.; Dandekar, Monisha N.; Naber, Stephen P.; Riesenburger, Ron I.
Highlights: Granular cell tumors (GCTs) are rare tumors of Schwann cell origin. GCTs have not been previously reported in the stellate ganglion. The differential for a mass of the stellate ganglion is discussed. The embryologic origins of these tumors are emphasized. Abstract: We report a granular cell tumor (GCT) that occurred within the stellate ganglion of a 26-year-old woman who initially presented with a unilateral Horner's syndrome and progressive right upper extremity pain. We also review the literature related to the differential diagnoses of such a cervicothoracic tumor, with particular emphasis on the embryologic origin of these possibilities. GCT are rare tumors of Schwann cell origin which are more often found in subcutaneous locations than in relation to neural elements. In this woman, a mass identified on preoperative imaging was positioned anterolateral to the T1 vertebral body and displaced the vertebral artery anteriorly. During surgery, the lesion was observed within the sympathetic chain in the area of the stellate ganglion. The sympathetic chain was transected above and below the mass in order to achieve an adequate resection. The pathology demonstrated polygonal cells with diffuse eosinophilic granular cytoplasm positive for CD68 (a marker of lysosomes) and S-100 (a marker of neural crest derivatives) which established the diagnosis of GCT. This is the first patient, to our knowledge, with a granular cell tumor arising from the stellate ganglion.